Educational experiences of hidden homeless teenagers : living doubled-up - Hallett, Ronald E. (New York, NY : Routledge, 2011)
'Homeless youth face countless barriers limiting their ability to complete a high school diploma and transition to postsecondary education. Their experiences vary widely based on family, access to social services, and where they live. More than half of the 1.5 million homeless youth in America are in fact living'doubled-up,' staying with family or friends because of economic hardship and often on the brink of full-on homelessness. Educational Experiences of Hidden Homeless Teenagers investigates the effects of these living situations on educational participation and higher education access. First-hand data from interviews, observations, and document analysis shed light on the experience of four doubled-up adolescents and their families. The author demonstrates how complex these residential situations are, while also identifying aspects of living doubled-up that encourage educational success. The findings of this powerful book will give students, researchers, and policymakers an invaluable look at how this understudied segment of the adolescent population navigates their education'-- Provided by publisher.
Includes bibliographical references and index.
Keywords: Homeless teenagers -- Education (Secondary) -- United States -- Case studies; Homeless teenagers -- Education (Higher) -- United States -- Case studies; Homeless teenagers -- Housing -- United States -- Case studies